Digital Transformation and Cultural Preservation: Virtual Reality (VR)-Based Gamelan Interaction in Ba-li, Lombok, and Yogyakarta - M Rikza Chamami; Muhammad Muntahibun Nafis; Ratna Kumala Dewi; Nisrin Mu'azzaz; Mohamad Aris Murtadho; Desi Dwi Anissa; Chasanatul Mardiyah; Syahma Laudza’i Rasyidah Shofina Ali (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
Digital transformation has brought new challenges and opportunities in cultural preservation in Indonesia, particularly through the application of Virtual Reality (VR) technology to the Gamelan tradition in Yogyakarta, Bali, and Lombok. This study highlights the urgency of cultural revitalisation and the transmission of traditional Gamelan values, which are increasingly being eroded by modernisation and changes in the lifestyles of the younger generation. Applied a qualitative approach and Design-Based Research (DBR) methods, this study examines local wisdom, structure, and the function of Gamelan through the Ethno-Stream model framework, which integrates science, technology, religion, engineering, art, and mathematics. Data were obtained through in-depth interviews with expert informants, Gamelan maestros, and cultural observers, as well as multimedia documentation. The study's results demonstrate that the development of an interactive VR-based Gamelan model has successfully increased cultural engagement and appreciation among the digital-native generation, thereby expanding the scope of learning across social, spiritual, and cultural domains. Analysis shows that immersive learning experiences through VR can bridge the generational gap in tradition and strengthen the global relevance of local culture. In conclusion, the integration of VR in Gamelan preservation can be an effective solution to enhance cultural identity, encourage multidisciplinary education, and build a sustainable model for cultural revitalisation in the digital age.